Can Social Customer Relationship Management Activities Evoke Customer Loyalty? (Study of Followers on the Twitter Account @gojekindonesia) - Trisha Lohanda; Agustinus Rusdianto Berto (BPSDMP Kominfo Jakarta, 2021)
Gojek is Indonesia's most significant creative economy industry that implements a Social Customer Relationship Management (CRM) strategy by utilizing Twitter to build interaction and engagement with its customers for long-term goals. This study aims to determine the influence of Social CRM activities undertaken by the @gojekindonesia Twitter account on customer loyalty. Therefore, this research surveyed 281 followers of the @gojekindonesia account, selected using a systematic random sampling technique. Statistical analysis of the collected data discovered some interesting findings. First, most of the followers are individual customers –only a few are drivers and merchants– who also use other similar competitor applications. Nonetheless, secondly, the regression analysis found a powerful influence on Gojek's SCRM activities in inducing their loyalty (83,5%), especially on @gojekindonesia's ability to identify context and sentiment in their content creation (analytic dimensions) which encourage active engagement of customers in using various services in Gojek application (customer value dimension). Keywords: customer loyalty; Gojek Indonesia; social customer relationship management; Twitter